EVALUATION OF THE SOCIAL BEHAVIOR OF ADOLESCENT STUDENTS AT SCHOOL - Darginidou, Lemonia (International Journal of Research -GRANTHAALAYAH, 2019)
The ability of adolescents to participate in the learning process at school requires a proper social behavior and social abilities such as cooperating skills, empathy and suspension of quick temperedness and disruptiveness. The aim of this research is to evaluate the social behavior of male and female students at school and study the influence of gender on factors of social behavior. The sample of the research consisted of 181 male and female students aged 12-13. The questionnaire used was the School Social Behavior Scale (SSBS), followed by a credibility analysis. T-tests were carried out, which confirmed the statistically important difference between the factor “quick temperedness” and the factor “gender”. The results of the research show that both male and female students present a positive social behavior, with the male students being more quick-tempered.